A call to the use of the clinical method in the practice of perinatal medicine - Carlos Esteban Zerquera Álvarez (Medisur)
A reflection on the appropriateness and current application of the clinical method, defined as the diagnostic process inherent to the practice of human medicine is presented. Considerations about the scientific nature of the clinical method and its application in perinatal medicine along with its specific characteristics in this field are stated. Several considerations about the impact of high technology and the risk of its use when the appropriate balance is not achieved, which could lead to dehumanization and medical malpractice are proposed.